Peritoneal Carcinomatosis: when everything is not what it seems - Perdigão, Sofia (2024)
Malignant peritoneal mesothelioma (MPM) is a rare neoplasm with a low incidence rate worldwide but high morbidity and mortality rates. Due to its rarity, the studies are scarce. We present a case of a 73-year-old woman admitted to the internal medicine unit with constitutional syndrome, abdominal pain, and ascites. Throughout the investigation, aspects suggestive of peritoneal carcinomatosis were identified. An extensive study was then carried out in an attempt to identify the primary tumor, which proved to be unsuccessful. During the two weeks of hospitalization, the patient's clinical condition worsened, with an increase in ascites and a deterioration in her general health. This case was then discussed with an oncology consultant, and it was decided to biopsy a peritoneal implant with the support of interventional radiology. MPM was then diagnosed through histopathology. With this case, the authors intend to highlight that, although rare, this diagnosis should be considered when appropriate and that even in the suspicion of secondary disease, the primary tumor should always be identified, as localized MPM may be curable.